Employee Performance And Motivation - Harun Samsuddin; Rasty Yulia; Soni Suharmono; Syamsu Rijal; Arief Yanto Rukmana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research approach is quantitative. The types of data used in this research are primary data and secondary data. Employees of PT Lotus Lingga Pratama receive questionnaires to collect primary data. Secondary data are collected indirectly, except from others or documents and journals related to this researcher. The population in this study is the entire permanent employee base of PT Lotus Lingga Pratama, which totals 153 employees. Motivation has a positive and significant influence on the performance of employees at PT. Lotus Lingga Pratama. Motivation is crucial and serves as a driving force for effort and goal achievement. Someone's doing something because of motivation. It can be understood that the higher the motivation, the higher the employee's performance.